A Comparative Analysis on Performance of TATA SAFARI and MAHINDRA XUV7OO among consumer Preference of Ahmedabad city. - Dhruv, Patel; Vatsal, Koladiya; Vidani, Jignesh (Contemporary Journal of Applied Sciences, 2024)
This study employed chi-square method to analyze the relation that exists between age and consumer preferences for Tata Safari and Mahindra XUV700 on vehicle attributes. The results showed that age affects preferences in design, performance, safety, fuel consumption and technology, as none of the p-values obtained for the majority of the posited hypotheses is less than the 0.05 level of significance. However, the older consumers had a strong perception that Mahindra XUV700 was better than Tata Safari, and it was found that p – 0.046 secrets of marketing about the inter-generational differences that relate to vehicle assessment factors like attributes trim, reliability and brand heritage. This provides evidence that not all aspects of traditional consumer models concerning demographic factors need to centre around the focalisation of marketing models, which models need to be broadened to include concepts of lifestyle and socio-economic sediment. Marketers have had their work cut out for them since different age group preferences have been established. There is a need for more future studies that will involve more diverse demographics, that take on more than one qualitative method and longitudinal studies to integrate